The Effect of Environmental, Social, and Governance (ESG) Performance on Corporate Financial Performance in Indonesia: Based on the Perspective of Innovation - Mardiana Mardiana; Tri Hanani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of environmental, social, and governance (ESG) performance on the financial performance of companies in Indonesia by considering innovation as a mediating variable and control variables, namely Earnings Per Share (EPS), Debt to Equity Ratio (DER), and Assets Growth. This study uses secondary data from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange. The analysis used multiple regression, mediation analysis, and control variable testing. The results show that ESG values ​​do not have a significant effect on Return on Assets (ROA), either directly or through innovation as a moderating variable. In addition, the control variables show that EPS, DER, and asset growth have a more dominant effect on ROA than ESG values. These findings indicate that the benefits of ESG on financial performance may not be visible in the short term. In contrast, the integration strategy of ESG and traditional financial indicators needs to be improved to produce a significant impact. This study provides important insights for corporate sustainability strategies in developing countries.